ULTRASONOGRAPY AND MAGNETIC RESONANCE IMAGING IN PATIENTS WITH SHOULDER PAIN - Ahmet Özgül,; M. Ali Taşkaynatan,; Ajda Bal,; T. Alp Kalyon, (Archives of Rheumatology, 2004)
The aim of this study was to put forward the possible etiology in shoulder pain with ultrasonography (USG). In patients with magnetic resonance imaging (MRI), the results of both imaging studies were compared, and the harmony of them was investigated. 96 patients with shoulder pain were examined prospectively with USG. The results of USG were compared with MRI findings in patients who had both imaging studies. The relation in all assessment parameters other than bicipital tendonitis/tenosynovitis (p>0.05) was statistically significant (p<0.05) when USG and MRI results were compared. The relation of bicipital tendonitis/tenosynovitis with supraspinatus partial and complete tear, subacromial bursitis and impingement in USG, and with only supraspinatus partial tear in MRI were statistically significant (p<0.05). As a conclusion, we suggest that USG is an effective and valid imaging method in diagnosis and follow up of shoulder pain. USG should be the first study in shoulder pathologies. MRI may be ordered in uncertain cases and if the patient is a surgery candidate.